Review of emergency obstetric hysterectomies at a tertiary care hospital - R., Renjini; R., Roshni; J., Simi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Emergency obstetric hysterectomy refers to surgical removal of pregnant or recently pregnant uterus with the pregnancy in utero or due to complications of delivery. This surgery is usually done as a last resort in life threatening obstetric hemorrhage. Objective of present study was to determine the incidence, sociodemographic and obstetric factors and indications associated with emergency obstetric hysterectomies. Methods: A retrospective, analytical study was conducted over a period of five years in the department of obstetrics and Gynecology of Government Medical college Thiruvananthapuram. Kerala. All cases of obstetric hysterectomy done during the study period in this hospital were analysed after getting approval from the institutional ethical committee. Results: During the study period there were total number of 78613 deliveries in SATH. Emergency obstetric hysterectomy was done for 86 cases. Obstetric hysterectomy rate in SATH during the study period was 0.109% or 1.09/1000 deliveries. Atonic postpartum hemorrhage (55%) was the most common indication followed by placenta praevia (27%). Majority were referred cases. Conclusions: Emergency obstetric hysterectomy can be a lifesaving procedure when other medical and surgical methods fail to control obstetric hemorrhage. This study highlights the unpredictable need of this procedure, need for identifying the at-risk cases and early referral to higher center.